Urban sustainability as a political instrument in the Gulf region exemplified by projects in Abu Dhabi - Cummings (née Deffner), Veronika; von Richthofen, Aurel (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The states of the Gulf Cooperation Council (GCC) are highly urbanised. The urban areas in the Gulf are nationally and internationally the focal point of economic development and political attention. Gulf cities are under rapid transformation and spaces of social, economic, ecological and political conflicts. While such dynamics gave rise to a differentiated debate on the political and social dimensions of urban sustainability in postindustrialised countries elsewhere, the narrative differs radically for the Gulf region. Urban sustainability in the Gulf will be discussed in this paper along three case-studies from Abu Dhabi that relate to the terminological and practical inception, adoption and transformation of the concept: The selected examples are modern residential neighbourhoods, the Abu Dhabi Vision 2030, and the eco-city model of Masdar. In combination with the general urban planning history of the city, these projects allow to trace the concept of urban sustainability in time and to understand its adoption into the Arabic language and the interrelations of the term to the Gulf regions’ specific political, ideological, and socio-cultural structures. Based on the works of Gunder (2006), Davidson (2010) and Brown (2016) the case studies reflect the concept of sustainability reduced to ‘sustainable development’. As such, it is becoming an ‘empty signifier’ that can be applied or instrumentalised by the ruling elites. This paper argues that the concept of urban sustainability in the Gulf is a foreign ‘import’ that serves in situ as a political instrument controlled by the ruling elites to stabilise the existing hegemonic power structures and to legitimise the political order.